Integration of blockchain and artificial intelligence as a mechanism for modernisation of various economic sectors - N. A. Kashevarova; M. E. Kulikova (Вестник университета)
The purpose of this article is to consider the prospects for the integration of blockchain and artificial intelligence (hereinafter referred to as AI) as an innovative approach to modernisation of various economic sectors. The authors analyse the possibilities of using this technological merger to optimise business processes, increase transparency and reduce transaction costs in different sectors, including finance, healthcare, transport, energy, etc. Particular attention is paid to the benefits of synergy between AI and distributed ledger technology, which allows for more efficient and sustainable systems of managing data and assets. The research object in this article is the process of integrating blockchain and AI. The subject of the study is the effectiveness of modernisation of various economic sectors through the combination of these technologies. The research method is an analytical review of scientific publications and successful implemented projects. The results of the current article lie in the analysis of the advantages of integrating blockchain and AI as well as forecasting further prospects for the development of this area. The practical significance of the work consists in the fact that the obtained results can be used to design strategies and plans for the implementation of this technology integration into domestic business.